Dokumentiranje navodil o življenjskem slogu in samoobvladovanju bolezni pri pacientih s kronično obstruktivno pljučno boleznijo - Ahačič, Maruša (Obzornik zdravstvene nege, 2018)
Introduction: To achieve a better quality of life in patients with chronic obstructive pulmonary disease, these patients should be informed about the characteristics of the disease and measures for its effective selfmanagement. The aim of the study was to determine the frequency and type of written instructions regarding lifestyle and self-management of the disease in hospital documentation of patients with chronic obstructive pulmonary disease. Methods: A retrospective quantitative study that reviewed all the hospital%s documents (therapy forms, nursing forms, archives of health education programmes, letters of discharge) was conducted including 253 patients with chronic obstructive pulmonary disease. The results were described in terms of descriptive statistics; chisquare test and ordinal logistic regression were used. Results: On average, hospital records of patients with chronic obstructive pulmonary disease showed less than 4 instructions (x = 3.8, s = 5.1) about life style and disease self-management. Half of chronic obstructive pulmonary disease patients received letters of discharge (x = 0.5, s = 0.9) which contained less guidance about lifestyle and self-management of the disease than their hospital records (x2 = 33.455, p < 0.001). Nurses recorded the instructions five times more frequently than doctors. Discussion and conclusion: The study showed a low number of written instructions about the life style and self-management of the disease given to chronic obstructive pulmonary disease patients during hospitalization. It is necessary to raise awareness about the importance of documenting health education instructions and design tools to improve inter-professional communication.
Keywords: documentation; dokumentacija; hospitalizacija; hospitalization; interprofessional collaboration; medpoklicno sodelovanje; pacienti; patients